Fluoroscopy and Dynamic Pressure-Based Foot Orthoses for Children With Flatfoot. Issue 2 (April 2019) - Liu, Xue-Cheng; Rizza, Robert; Van Valin, Scott; Al-Ramahi, Jehad; Lyon, Roger; Thometz, John
ABSTRACT: Introduction: The current nonsurgical treatment for pediatric flatfoot includes shoe modification, inserts, and foot orthoses (FOs). However, these methods do not affect the course of flatfoot in children and have only limited evidence of correction of foot pronation. The goals of this study are 1) to describe how to design novel customized FOs using plantar pressure and fluoroscopic measurements; and 2) to assess kinematics and kinetics of the foot and ankle joint and functional outcomes at baseline and 12-month follow-up. Materials and Methods: One child with bilateral flatfeet received trio-pressure measurements, including dynamic plantar pressure, single sensor pressures on the lateral calcaneus, and medial talar head. The two-dimensional (2D) foot motion in the sagittal plane during the stance phase using single gantry fluoroscopy was recorded. Three-dimensional (3D) surface images of the entire foot and distal lower limb were registered. Results: A total of 14 pressure metrics and three-dimensional (3D) foot and ankle topography were used to design the new orthoses and generate a computer-aided design model. Data from the fluoroscopic images were used to evaluate the orthotic design. Finally, two orthoses were designed and manufactured with a rapid prototype system (SLS). Discussion: The gait-based software was successfully developed to design the new orthoses. Features included use of navicular height, talar and calcaneal alignment, pressure metrics, and foot geometry. This case study had 12-month follow-up and showed that the new FOs reduced pain and improved functional outcomes. Conclusions: Use of gait-based software allows a further approach directly into the rapid prototype systems for orthoses designed to address pes valgus deformity.